PENANAMAN NILAI K ARAKTER MELALUI KEGIATAN TAHFIDZ DI SDN 22 LINTAU BUO UTARA - Endriani, Budi; Dayu, Refni (JISPE Journal of Islamic Primary Education, 2023)
This study aims to describe the cultivation of character values through tahfidz activities at SDN 22 Lintau Buo Utara. The research method used in this study is field research, with a qualitative approach. The data collection techniques used are observation, interviews, and documentation. Source of research data from the principal and Teacher tahfidz of the Qur'an. The data analysis technique used is an inductive data analysis technique. The validity of the data used is trianggulation. Research Results are 1) The methods used in the implementation of the cultivation of character values are habituation, supervision and attention, the methods used in the activities of tahfidz of the Qur'an i.e. the sima'i method. 2) The character values instilled through Tahfidz activities are values, religious and responsibility this can be seen from the attitudes of students who carry out duha prayers, and zuhur congregational prayers before tahfidz activities are carried out. 3) The form of implementation of the cultivation of character values through activities, namely with the addition of extracurricular tahfidz in Utaras, 4) Synergy of parents towards the cultivation of character values in students through activities, Tahfidz Al-Qur'an can be seen communication and coordination in parents at home. Obstacles faced by some students who do not like to read the Qur'an.